Security, development, protection. The triptych of externalization migration policies in Niger - (:unkn) unknown (My University, 2019)
Circulation space between the north and the south of Sahara, Niger is becoming since the end of the 2000s, the main crossing point for West African migrants to Algeria, Libya and even Europe. In addition to this crossing position, Niger is also a departure space for circular migrants, who leave in search of a temporary activity in North and West Africa. This particular position, as well as the instability in Libya since 2011, contribute to make it a key country for European externalization policies, that was put in place from the Valletta Summit in 2015. In just a few years, the interventions of European and international actors (IOM, UNHCR) have led to the implementation of devices articulated around security, development and protection. Firstly, the border and movements control, secondly projects aimed at stabilizing populations, and thirdly the building of a protection space in Niger, contribute to make it a contention and blocking space for people on the move.
Keywords: African Research